Investment analysis and price formation in securities markets - Brennan, Michael J.; Subrahmanyam, Avanidhar (Journal of Financial Economics, 1995)
This paper investigates the relation between the number of analysts following a security and the estimated adverse selection cost of transacting in the security, controlling for the effects of previously identified determinants of liquidity. Using intraday data for the year 1988, we find that greater analyst following tends to reduce adverse selection costs based on the Kyle (1985) notion of market depth. This result is consistent with the analysis of Admati and Pfleiderer (1988). Estimates of structural parameters of a version of the Admati and Pfleiderer model of endogenous information acquisition provide qualified support for the model.